Inter-connected coupled lines Resonator topology for bandpass filter application - Mohd Nasiruddin Hushim; Norfishah Ab Wahab; Tn. Syarifah Atifah Tn. Mat Zin; Norlia Ghazali (Institute of Advanced Engineering and Science, 2020)
This paper presents an inter-connected side-shorted coupled-line resonator topology as a base cell. The base cell is built from two single-shorted quarter-wavelength coupled-line sections, connected in series to give a half-wavelength coupled-line that creates a single resonance of bandpass filter response. Higher-order bandpass filter is produced by adding new single-shorted coupled-line sections, cascaded in an inter-connected manner to the base cell. This new topology creates a unique arrangement that caused cross coupling effects between the resonators, resulting to the occurrence of transmission zeros that lead to the improvement of selectivity of the higher order bandpass filter response. For validation of concept, 2nd and 3rd order bandpass filters were fabricated using microstrip technology on Roger 3210 substrate with parameter of Ɛr = 10.2, h = 1.27 mm and tan δ = 3x10-3. The filters were measured and the results show good agreement with simulation results.